2013
DOI: 10.1080/00909882.2012.744076
|View full text |Cite
|
Sign up to set email alerts
|

A Game-Theoretic Model of Disclosure–Donation Interactions in the Market for Charitable Contributions

Abstract: The information organizations choose to disclose is a strategic consideration. The ''success'' of strategic disclosure is contingent in turn on the target audience's values and preferences. The disclosure of and reaction to organizational information thus involves a strategic interaction between the producer and consumer of the information, yet prior communication research has focused on only one side or the other of this equation. In response, we examine organizationÁpublic interactions in a domain with key, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
14
1
3
Order By: Relevance
“…Each type of disclosure practice is discussed separately in the next three sections. Previous empirical studies have found a positive relationship between the extent of disclosure and total donations (Parsons, 2003; Saxton & Zhuang, 2013; Trussel & Parsons, 2008; van der Heijden, 2013).…”
Section: Information Disclosure Of Nonprofits and Signaling Theorymentioning
confidence: 89%
See 1 more Smart Citation
“…Each type of disclosure practice is discussed separately in the next three sections. Previous empirical studies have found a positive relationship between the extent of disclosure and total donations (Parsons, 2003; Saxton & Zhuang, 2013; Trussel & Parsons, 2008; van der Heijden, 2013).…”
Section: Information Disclosure Of Nonprofits and Signaling Theorymentioning
confidence: 89%
“…Extending from the empirical literature, Saxton and Zhuang (2013) used game theory to model the relationship between nonprofit disclosure and donations. Saxton and Zhuang defined efficiency using programming spend ratios, which tap into the proportion nonprofits spend on programs as opposed to fundraising or administration.…”
Section: Information Disclosure Of Nonprofits and Signaling Theorymentioning
confidence: 99%
“…One of the most persuasive means used to draw in donations is creating a perception of a personal connection for the donor to make donors feel as if they make a difference. Having an impact is important to donors (Saxton & Zhuang, 2013). Clair and Anderson (2012) show Kiva’s use of the personal-connection-form of advertising in which donors are led to believe that they may pick the person to whom they wish to have their loan/donation sent, backfired when it was revealed that no such practice was taking place; instead, Kiva bundles the money and supplies it to the Grameen Bank., The revelation triggered “over 10,000 hits and thousands of twitter postings” from disgruntled donors (Strom, 2009, n.p.).…”
Section: Charitable Organizations On the Cusp Of Capitalismmentioning
confidence: 99%
“…The illusion of limited resources is important for a nonprofit’s legitimacy. As Saxton and Zhuang (2013) pointed out, people measure the legitimacy of the nonprofit by ratio of proceeds disbursed to the money spent on overhead.…”
Section: Charitable Organizations On the Cusp Of Capitalismmentioning
confidence: 99%
“…Game theory is the study of mathematical models of conflict and cooperation among decision-makers (Myerson 1997). It is mainly used in political science (Downs 1957;Hausken and Zhuang forthcoming), logic (Smith and Price 1973), biology (Ben-David et al 1994), psychology (Colman 2003;Xu and Zhuang, forthcoming), donation (Zhuang et al 2014;Saxton and Zhuang 2013), and economics (Aparicio and Sanchez-Soriano 2008;Agarwal and Zeephongsekul 2011). Researchers apply game theory to study security problems, such as optimization of resource allocation (Xu et al forthcoming; Xiang and Zhuang forthcoming).…”
Section: Introductionmentioning
confidence: 98%